Konsep Penegakan Hukum Pidana Adat di Indonesia Berdasarkan Asas Kepastian Hukum - Bahri, Robi Assadul (Law, Development and Justice Review, 2024)
One of the advances in Indonesian criminal law is the recognition of customary criminal law in the New Criminal Code. However, there will be problems in enforcing national criminal law if customary criminal law is accommodated. The problem that will be studied in this research is the consequences of the implementation of customary criminal law in enforcing national criminal law and enforcing customary criminal law in Indonesia that has legal certainty. This research is legal research with a typology of normative/doctrinal legal research which aims to produce a new argument, theory or concept on the problem being studied. The research results show that the application of customary criminal law in enforcing national criminal law will have the potential for disharmonious relations between law enforcement officials and local customary institutions. Therefore, enforcement of customary criminal law in Indonesia with legal certainty can be achieved by reviving the Customary Courts which have the authority to examine and try violations of customary criminal law. This research recommends immediately compiling customary law through regional regulations and immediately enacting a Draft Law on Customary Courts to ensure legal certainty of customary justice in the Indonesian Judicial System.